Multifidelity design of low-thrust resonant captures for near-Earth asteroids - Neves, Rita; Sánchez, Joan-Pau (AIAA, 2018)
The design of a space trajectory is strongly linked to the gravitational and non-gravitational environment and the dynamical frameworks required to model it. These dynamical models may range from low to high fidelity, with corresponding computational costs. This paper proposes a multifidelity approach for the computation of nearly resonant trajectories with the Earth. This framework is used to compute trajectories for the capture of near-Earth asteroids into libration point orbits of the Sun – Earth system. The transfer is first computed in a suitable low-fidelity model, the Keplerian map, and a multifidelity approach is subsequently used to refine the solution from an impulsive approximation into a low-thrust transfer in the circular restricted three-bodyproblem. The entire trajectory follows a nearly resonant motion with the Earth, lasting less than two synodic periods; starting when the retrieval spacecraft attaches itself to the asteroid, they will encounter the Earth twice, being captured into the target orbit at the end of the second encounter. A velocity change maneuver is carried out at the beginning of the motion, so that the first encounter with the Earth provides a gravitational perturbation resulting on a reduction of overall propellant costs of the transfer. The developed framework is very flexible in terms of the desired accuracy and allows for the low computational cost exploration of a vast number of possible trajectories. The obtained low-thrust transfers yield, for six asteroids, a much higher retrievable mass in comparison with direct capture trajectories, which do not undertake Earth-resonant encounters.